Pengaruh variasi milling terhadap strukturmikro dan kekerasan paduan serbuk Fe-C dengan metode mechanical alloying - Aleksander Jehatu; Sutrisna; Mustakim; Dandung Rudy Hartana (ReTII, 2024)
This study aims to investigate the effect of varying milling durations (4 hours, 8 hours, and 12 hours) on the microstructure and hardness of Fe-C alloy powders processed using the mechanical alloying method. The mechanical alloying process involves high-energy milling to produce a homogeneous mixture with fine grain size. The variation in milling duration is expected to influence microstructural changes, such as grain size, phase distribution, and the formation of metastable phases. Microstructural analysis was conducted using electron microscopy. The results show that longer milling durations lead to finer grain sizes and an increase in martensitic phase formation. At 12 hours of milling, the grain size reached the nanometer scale, contributing to increased hardness (425 HVN) and microstructural homogeneity. Thus, the variation in milling duration significantly impacts the microstructural evolution of Fe-C alloy, with longer milling durations producing finer and more uniform microstructures. This research provides deeper insights into the relationship between milling parameters and the microstructural properties of Fe-C alloy for more optimal applications in engineering materials. .